The Sec14-like phosphatidylinositol transfer proteins Sec14l3/SEC14L2 act as GTPase proteins to mediate Wnt/Ca2+ signaling - Bo Gong; Weimin Shen; Wanghua Xiao; Yaping Meng; Anming Meng; Shunji Jia (eLife, 2017)
The non-canonical Wnt/Ca2+ signaling pathway plays important roles in embryonic development, tissue formation and diseases. However, it is unclear how the Wnt ligand-stimulated, G protein-coupled receptor Frizzled activates phospholipases for calcium release. Here, we report that the zebrafish/human phosphatidylinositol transfer protein Sec14l3/SEC14L2 act as GTPase proteins to transduce Wnt signals from Frizzled to phospholipase C (PLC). Depletion of sec14l3 attenuates Wnt/Ca2+ responsive activity and causes convergent and extension (CE) defects in zebrafish embryos. Biochemical analyses in mammalian cells indicate that Sec14l3-GDP forms complex with Frizzled and Dishevelled; Wnt ligand binding of Frizzled induces translocation of Sec14l3 to the plasma membrane; and then Sec14l3-GTP binds to and activates phospholipase Cδ4a (Plcδ4a); subsequently, Plcδ4a initiates phosphatidylinositol-4,5-bisphosphate (PIP2) signaling, ultimately stimulating calcium release. Furthermore, Plcδ4a can act as a GTPase-activating protein to accelerate the hydrolysis of Sec14l3-bound GTP to GDP. Our data provide a new insight into GTPase protein-coupled Wnt/Ca2+ signaling transduction.